Pelayanan Pelanggan Melalui Balanced Scorecard untuk Mencapai Tujuan Pendidikan - Rohman Rohman; Neneng Komariah; Oo Sodikin; Iim Wasliman; Supyan Sauri (Foramadiahi: Jurnal Kajian Pendidikan dan Keislaman, 2022)
Customers are important for the running of an institution. Customers determine the existence of an institution. For this reason, service to customers and maintaining relationships with customers is a must, as Peters and Waterman argued: an excellent organization is an organization that can maintain relationships with its customers and has an obsession with quality. Customers are all people who demand the company to meet a certain quality standard that will have an influence on the company's performance and company management. Principals must provide excellent service to all customers so that educational goals can be achieved efficiently and effectively. To measure customer satisfaction with the principal's service, you can use the Balanced Scorecard (BSC) so that deficiencies in service can be minimized. It is so important to use the Balanced Scorecard (BSC) that the author tries to do a research with the title of Customer Perspective Development through the Balanced Scorecard (BSC). With the aim of providing enlightenment on how to develop a customer perspective through the Balanced Scorecard (BSC) so that the services provided to customers can be moreeffective and efficient to achieve educational goals.